2005
DOI: 10.1590/s0100-67622005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Purificação e caracterização de alfa-galactosidases de sementes de Platymiscium pubescens Micheli

Abstract: 2RESUMO -Este trabalho objetivou foi determinar a composição bioquímica de sementes de espécies florestais e caracterizar a enzima α-galactosidase de sementes germinadas de Platymiscium pubescens. Os maiores teores de lipídios foram determinados em sementes de Chorisia speciosa, Caesalpinia peltophoroides, Tabebuia serratifolia e Tabebuia velanedae, enquanto sementes de Enterolobium contortisiliquum, Schizolobium parahyba e Cassia grandis apresentaram os maiores teores protéicos. A α-galactosidase catalisa a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
1
1
1
Order By: Relevance
“…According to Borges et al (2005), -galactosidase is active in Caesalpinia peltophoroides seeds even before imbibition and increases activity with imbibition, being higher in the embryonic axis than in cotyledons. Oliveira et al (2006) observed that the specific activity of -galactosidase in seeds of Platymiscium pubescens and Senna macranthera, differently to results in this work, decreased after 96 h of imbibition. Comparing Figure 4 data to results obtained for monosaccharides, no relationship is noted between enzyme activity and absence of galactose, a component of galactomannan, a substrate of -galactosidase.…”
Section: Carrijo L C Et Alcontrasting
confidence: 70%
“…According to Borges et al (2005), -galactosidase is active in Caesalpinia peltophoroides seeds even before imbibition and increases activity with imbibition, being higher in the embryonic axis than in cotyledons. Oliveira et al (2006) observed that the specific activity of -galactosidase in seeds of Platymiscium pubescens and Senna macranthera, differently to results in this work, decreased after 96 h of imbibition. Comparing Figure 4 data to results obtained for monosaccharides, no relationship is noted between enzyme activity and absence of galactose, a component of galactomannan, a substrate of -galactosidase.…”
Section: Carrijo L C Et Alcontrasting
confidence: 70%
“…O teor mais elevado de lipídio foi obtido quando as sementes atingiram a maturidade fisiológica (23,6 g 100 g -1 ), que é superior ao encontrado por Oliveira et al (2005) para Platymiscium pubescens Micheli, espécie de cerrado (4,67 g 100 g -1 ). Nas sementes colhidas em desenvolvimento de P. floribundum (agosto de 2004), o valor encontrado foi de 13,0 g 100 g -1 (TABELA 1).…”
Section: Resultsunclassified
“…a-Galactosidase activity was determined using a synthetic substrate, p-nitrofenyl-a-D-galactopyranoside (pNPaGal) (Oliveira et al, 2005). The assay system contained 750 lL of 100 mM sodium acetate buffer, pH 5.0, 100 lL of enzyme preparation and 250 lL 2 mM p-nitrofenyl-a-D-galactopyranoside.…”
Section: Enzymatic Assaymentioning
confidence: 99%